Can number of platelets, blood red cell distribution, volume of neutrophil/lymphocyte ratio and mean platelet volume in patients with systemic lupus erythematosus and sjögren be used as an inflammation marker? - Gülkesen, Arif; Gozel, Nevzat (My University, 2019)
Sjögren’s syndrome (SS) and systemic lupus erythematosus (SLE) are autoimmune rheumatic diseases that can cause significant organ involvements. Hematological indices such as Platelet Count (PLT), Blood Red Cell Distribution Volume (RDW), Neutrophil/Lymphocyte Ratio (NLR), and Mean Platelet Volume (MPV) can be assessed by a simple haemogram test. These parameters may be related to the activity of the patient’s other diseases, such as cardiovascular diseases and inflammatory diseases. Our aim in this study is to demonstrate the possible association of hematologic markers such as PLT, RDW, NLR, MPV with the disease activity. 40 patients diagnosed with SS and 40 patients diagnosed with SLE followed in the physical medicine and rehabilitation and internal medicine rheumatology polyclinics and 40 healthy volunteers were included in the study. Laboratory findings were obtained from routine polyclinic controls. RDW, MPV, NLR ratios and platelet counts were calculated from the results of whole blood counts (CBC). RDW, MPV, NLR, and PLT were expressed as medians (minimum-maximum). Epidemiological data and RDW, MPV, NLR, PLT values of the cases included in the study were compared. Among the patients with SS and SLE, RDW, NLR and MPV values were higher than in the healthy control group. However, the elevation in the RDW was statistically significant while the height in the MPV and NLR was not statistically significant. Although studies with further patient participation are necessary, hematologic markers can be used in the diagnosis and follow-up of rheumatic diseases as they are both inexpensive and can be utilized extensively.
Keywords: Genel ve Dahili Tıp; Hematoloji; Romatoloji